The Role of Government Strategy in Encouraging Women's Empowerment in the Digital Era - Misrina; Mega Fitri Hertini (CV. Era Digital Nusantara, 2026)
The rise of digital technology has created new opportunities for women's empowerment, yet structural and cultural barriers continue to hinder their full participation. This study aims to analyze government strategies in promoting women's empowerment in the digital era through policies, digital literacy training, and cross-sector collaboration. A descriptive qualitative literature review method was employed, drawing from journals, reports, and policy documents. Findings reveal that community-based digital training, technological access, and regulatory support are effective in enhancing women's roles in the digital economy. Nevertheless, challenges such as the digital divide, gender stereotypes, and limited financial access remain significant obstacles. The study concludes that inclusive policies and sustained programs are crucial to enabling women to thrive in the digital transformation. It is recommended that the government expand training programs and strengthen partnerships with the private sector to build a gender-equal digital ecosystem